Tuk-Utuk Culture and Improvement Madura Community Welfare - Syaful Anam; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
Talking about the problem of tuk-tuk, we talk about cultural issues, because tuk-tuk has become a culture, especially for the Madurese community. Culture has many meanings, one of which is a way of life that develops and is shared by a group of people, and is passed down from generation to generation. This study aims to see the relationship or correlation between the tuk tuk culture and improving the welfare of the Madurese community. Then the results of this study reveal that the tuk utuk culture can lift the economy of active members of utuk-utuk and the Madurese community of course. With the capital obtained from tuk-tuk, we are able to manage it so that it can develop a bigger business, so that it can increase welfare both individually and as a community.